Pemahaman Masyarakat Indonesia Terhadap Kata Bahasa Arab Yang Sudah Diserap Ke Dalam Bahasa Indonesia: Studi Kasus Kata-Kata Yang Berhubungan Dengan Kematian - Andre Riswanda; Ganjar Eka Subakti (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2022)
The study aims to illustrate and discover how the influence of Arabic uptake on the development of Indonesian now focused on how Indonesian culture is in terms related to death in everyday life. The method used in this study is a literature review using a descriptive qualitative approach. The data sources in this study are books or writings either in writing or on social networks related to research objects including dictionaries Indonesian and other books. The results showed that the influence of Arabic on Indonesian language is quite large. This can be seen from how the use of language in Indonesia that uses a lot of arabic uptake language, one of which is in the ritual of death.